2014
DOI: 10.1111/febs.12741
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic galactokinase expression underlies GAL gene induction in a GAL3 mutant of Saccharomyces cerevisiae

Abstract: GAL1 and GAL3 are paralogous signal transducers that functionally inactivate Gal80p to activate the Gal4p-dependent transcriptional activation of GAL genes in Saccharomyces cerevisiae in response to galactose. Unlike a wild-type strain, the gal3Δ strain shows delayed growth kinetics as a result of the signaling function of GAL1. The mechanism ensuring that GAL1 is eventually expressed to turn on the GAL switch in the gal3Δ strain remains a paradox. Using galactose and histidine growth complementation assays, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 77 publications
(86 reference statements)
4
18
0
Order By: Relevance
“…In contrast, we observed a 7–18% survival rate on selection of the isogenic progeny ( Table 4 and Table S2 ). These results support the involvement of a nongenetic event in the galactose-tolerant phenotype of the two original euploid strains, possibly deriving from cell-to-cell differences in intracellular protein or transporter levels ( Acar et al 2005 ; Kar et al 2014 ). We further found that single cells from clonal populations of galactose-tolerant progeny also demonstrated low survival rates when grown on galactose medium, suggesting that this nongenetic event could affect mitotically dividing cells as well as germinating spores ( Table S2 ).…”
Section: Resultssupporting
confidence: 77%
“…In contrast, we observed a 7–18% survival rate on selection of the isogenic progeny ( Table 4 and Table S2 ). These results support the involvement of a nongenetic event in the galactose-tolerant phenotype of the two original euploid strains, possibly deriving from cell-to-cell differences in intracellular protein or transporter levels ( Acar et al 2005 ; Kar et al 2014 ). We further found that single cells from clonal populations of galactose-tolerant progeny also demonstrated low survival rates when grown on galactose medium, suggesting that this nongenetic event could affect mitotically dividing cells as well as germinating spores ( Table S2 ).…”
Section: Resultssupporting
confidence: 77%
“…In a wild type yeast strain (W303) bearing a GFP reporter gene expressed from the GAL1 promoter we find that ~80% of cells induce significant GFP expression within an hour of galactose addition, and greater than 95% become fully induced within 4 hours (Figure 1A). In contrast, consistent with previous observations (33), only a minor subset of gal3 yeast induce GFP expression even at 24 hours, and after 96 hours only ~10% of the cells induce significant expression (Figure 1B). Importantly however, individual gal3 cells are capable of inducing GFP expression comparable to levels similar to wild type.…”
Section: A Minor Subset Of Gal3 Yeast Induce Full Gal Expression In Rsupporting
confidence: 93%
“…In non-inducing conditions, GAL3 is basally expressed, whereas GAL1 transcription is repressed, with the result that Gal3p is the main galactose sensor. Importantly, in cells where Gal3p is absent or in cells with previous exposure to galactose, Gal1p becomes the primary sensor of galactose (Abramczyk et al, 2012; Kar et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Stains with a GAL3 deletion exhibit a partial penetrance phenotype in which growth on galactose is dependent on GAL1 leakage (Kar et al, 2014). We find that after GAL10 ncRNA inhibition, gal3 Δ strains grow faster on galactose containing plates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation